The role of social group influences when intending to purchase premium alcohol - Nicole Cunningham (Cogent Business & Management, 2023)
This study investigates the effect that social group influences have on the purchase intention of premium alcohol by adapting the theory of planned behaviour. The moderating effect of the need to save face and conform to a social group's expectations on the purchase intention of premium alcohol is explored. Data was collected using questionnaires, with 251 responses analysed using the PLS-SEM. The results show that attitude and subjective norms have a positive and significant impact on the purchase intention of premium alcohol, while perceived behavioural control does not. Brand consciousness and status consumption were found to have an impact on attitude and subjective norms respectively, with status consumption revealing the strongest relationship. This study offers insight to both researchers by understanding the impact of social influences and to premium alcohol brands that would be able to further enhance their marketing strategies and resonate with consumers in a highly competitive environment.
Keywords: 650; purchase intention; Premium alcohol; social influences; status